Lung resection after neoadjuvant chemoimmunotherapy: a narrative review - Chu, Ngoc-Quynh; Gibney, Barry C. (Video-Assisted Thoracic Surgery, 2026)
Background and Objective: The treatment landscape for non-small cell lung cancer (NSCLC) is dynamic and rapidly evolving. The success of chemoimmunotherapy for early-stage and resectable disease has improved oncologic outcomes while introducing new surgical challenges. This review examines key considerations and the existing literature on surgery in the era of neoadjuvant chemoimmunotherapy.Methods: Clinical studies, reviews, and guidelines on the topic of surgery/lung resection after neoadjuvant chemoimmunotherapy (excluding neoadjuvant radiation) were selected and reviewed based on an electronic search in PubMed and Google Scholar. English-language literatures published in 2000 and onwards were included, as were referenced publications cited within relevant articles. Publications were selected based on relevance and currency to the objectives of the review.Key Content and Findings: Superior oncologic outcomes with the use of neoadjuvant chemoimmunotherapy for resectable NSCLC have been consistently demonstrated by several randomized controlled trials. Lung resection in this setting is shown to be safe and feasible, but has also raised new challenges for clinical and surgical decision making. These considerations include (I) determination of resectability; (II) assessing response to neoadjuvant treatment and timing of surgery; (III) technical challenges and surgical outcomes; and (IV) application of minimally invasive techniques.Conclusions: High-level evidence supports the use of neoadjuvant chemoimmunotherapy in the treatment of resectable NSCLC. Surgery will see an expanding role within this paradigm shift and requires that surgeons understand the challenges and opportunities in the care of these patients.